Pro-inflammatory Monocyte Phenotype During Acute Progression of Cerebral Small Vessel Disease - Noz, Marlies P.; Telgte, Annemieke ter; Wiegertjes, Kim; Tuladhar, Anil M.; Kaffa, Charlotte; Kersten, Simone; Bekkering, Siroon; van der Heijden, Charlotte D. C. C.; Hoischen, Alexander; Joosten, Leo A. B.; Netea, Mihai G.; Duering, Marco; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The etiology of cerebral small vessel disease (SVD) remains elusive, though evidence is accumulating that inflammation contributes to its pathophysiology. We recently showed retrospectively that pro-inflammatory monocytes are associated with the long-term progression of white matter hyperintensities (WMHs). In this prospective high-frequency imaging study, we hypothesize that the incidence of SVD progression coincides with a pro-inflammatory monocyte phenotype. Methods: Individuals with SVD underwent monthly magnetic resonance imaging (MRI) for 10 consecutive months to detect SVD progression, defined as acute diffusion-weighted imaging-positive (DWI+) lesions, incident microbleeds, incident lacunes, and WMH progression. Circulating inflammatory markers were measured, cytokine production capacity of monocytes was assessed after ex vivo stimulation, and RNA sequencing was performed on isolated monocytes in a subset of participants. Results: 13 out of 35 individuals developed SVD progression (70 ± 6 years, 54% men) based on incident lesions (n = 7) and/or upper quartile WMH progression (n = 9). Circulating E-selectin concentration (p < 0.05) and the cytokine production capacity of interleukin (IL)-1β and IL-6 (p < 0.01) were higher in individuals with SVD progression. Moreover, RNA sequencing revealed a pro-inflammatory monocyte signature including genes involved in myelination, blood–brain barrier, and endothelial–leukocyte interaction. Conclusions: Circulating monocytes of individuals with progressive SVD have an inflammatory phenotype, characterized by an increased cytokine production capacity and a pro-inflammatory transcriptional signature.